2011
DOI: 10.2215/cjn.03350411
|View full text |Cite
|
Sign up to set email alerts
|

Serum Free Light Chains and the Risk of ESRD and Death in CKD

Abstract: SummaryBackground and objectives Associations between inflammation and ESRD and death in chronic kidney disease are well established. However, the potential role of the adaptive immune system is uncertain. We aimed to prospectively study the relevance of the adaptive immune system to ESRD and mortality by measuring monoclonal and polyclonal excesses of highly sensitive serum free light chains (sFLCs).Design, setting, participants, & measurements Three hundred sixty-four patients selected from a nephrology outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 40 publications
2
42
1
1
Order By: Relevance
“…This stronger association of FLC than CRP with clinical outcomes has also been shown in other studies that have used CRP and cFLC (14,15). We have recently shown that the kinetics of CRP and cFLC levels in disease states differ, with CRP levels more closely associated with acute inflammation and FLC associated with chronic inflammation (28).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This stronger association of FLC than CRP with clinical outcomes has also been shown in other studies that have used CRP and cFLC (14,15). We have recently shown that the kinetics of CRP and cFLC levels in disease states differ, with CRP levels more closely associated with acute inflammation and FLC associated with chronic inflammation (28).…”
Section: Discussionsupporting
confidence: 80%
“…In an analysis of the Chronic Renal Impairment in Birmingham Study data, there was a weak independent association with polyclonal lFLC in a multivariable model that included troponin and N-terminal pro brain natriuretic peptide (14). However, this cohort included patients with a higher degree of comorbidity and more advanced CKD (mean eGFR=21.9 ml/min per 1.73 m 2 ) compared with this study population.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations